Physical science : with environmental applications - Wiggins, Arthur W. (Boston : Houghton Mifflin, 1974)
The study guide which goes along with this book contains supplementary material for the student who is having difficulty and challenging material for the student who finds the material too easy.
One. What is physical science all about? -- Two. What is matter made of? -- Three. How far apart are the atoms in solid matter? -- Four. What holds the atoms in place in solid matter? -- Five. Putting together the various kinds of solid matter.
Includes index.
Keywords: MATTER; PHYSICS